Management of Quality in Logistics Centers of The Middle Pomerania Region - Joanna DYCZKOWSKA; Marcin OLKIEWICZ (Communications of International Proceedings, 2022)
Logistics Centers (LCs) are an important part of the modern logistics system, and their selection by customers has become a key issue in logistics and supply chain management. Integrating the economic, environmental and social dimensions of sustainability, the article presents a new LCs quality assessment system from a 5S perspective. Logistics centers (LCs) of operators operating in various regions of the country, including Middle Pomerania in the development of logistics services are gaining key importance. The purpose of the article was to examine the quality of services provided by selected operator logistics centers in Middle Pomerania. To test the logistics services quality observations and 5S method was used. This analysis is aimed at carrying out internal changes in LCs and introducing excellence in logistics services and improving customer satisfaction with logistics services provided by the logistics provider.
Keywords: logistics centers (LCs); management; 5S; quality